ANALISIS DAN PERANCANGAN SISTEM PENGOLAHAN DATA KEPEGAWAIAN DI KANTOR BPMPT KOTA SURAKARTA - Firdhaus Hari Saputro Al Haris; Dwi Retnoningsih; Nugroho Tri Wibowo (Universitas Sahid Surakarta, 2014)
In the era of globalization is very big influence on the advancement of technology a company or government. Office of Badan Penanaman Modal dan Perizinan Terpadu(BPMPT) Surakarta one of the government agencies that have always wanted to follow the development of information technology is growing. Archive management personnel data for this is still not good so the search for the data to be inefficient in terms of time and effort, the data is not stored properly because it uses a sheet of paper that is easily torn, the data are easily lost, easily damaged and recording employee data are still using Ms Excel making it less efficient. The research objective is to produce a computerized system in the Office of Personnel Data BPMPT Surakarta created to facilitate the search for archived data Personnel. Methods of data collection in this study using the method of observation and interviews, while the method of system development using sequential Linear Model /Waterfall Model. The system is built using the PHP programming language and MySQL database and system testing using blackbox testing methods. The results of the new system is a new system that can facilitate the delivery of information personnel data and search archive of personnel data. Archive of personneldata can be reprinted as desired. From the test results, it appears that the 100% (one hundred percent) functional run in accordance with the test scenario and the system isable to facilitate the Officers in BPMPT Office manage archives staffing data and information delivery personnel data, with this system, able to facilitate the search forarchive personnel data, especially data that long.